Creating a Federal Inmate Grievance Tribunal - Patrick, Jeremy (Canadian journal of criminology and criminal justice, 2006)
Federal inmates in Canada currently have access to a wide variety of mechanisms that purport to ensure their rights are respected: internal grievance systems, the Canadian Human Rights Commission, the Office of the Correctional Investigator, the court system, and more. However, for a variety of reasons, each of these mechanisms is inadequate to import accountability and the rule of law into the prison system. Instead, this article proposes the creation of a Federal Inmate Grievance Tribunal to rule on the merits of selected grievances. Key features of the proposed tribunal include fairness and independence; timely resolution of cases; and the ability to issue binding orders. In addition, the structure of the proposed tribunal is discussed. (English) [ABSTRACT FROM AUTHOR]